Cytotoxicity of Clinacanthus Nutans Extracts on Human Hepatoma (HepG2) Cell Line - Hazrulrizawati, Hamid; Izzah Hayati, Yahaya (Innovare Academic Sciences, 2016)
Objective: Clinacanthus nutans is one of the herbs that has been used in Asia as a traditional medicine for the treatment of serious diseases. The aim of this study is to investigate the phytochemical constituents (flavonoids and phenolics) and cytotoxicity against human hepatoma (HepG2) cancer cell lines of C. nutans extracts. Methods: The fractions from C. nutans were extracted from hexane, methanol, chloroform and ethyl acetate by the solvent-solvent extraction method. The crude extracts (10 mg/ml) were tested against HepG2 cell lines using 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Phytochemical screening was done to determine the total phenolic content (TPC) and total flavonoid content (TFC). Results: Methanol extract showed the strongest cytotoxic activity against HepG2 cell line with IC 50 of 43.9367μg/ml after 24 h of treatment compared to chloroform extract and ethyl acetate, 55.6112µg/ml and 62.0655µg/ml, respectively. Hexane extract formed the lowest cytotoxicity activity with IC50 of 68.3807µg/ml. Total phenolic content (TPC) was found to be highest in chloroform, which was 119.29 mg of gallic acid equivalent (GAE) and total flavonoid content (TFC), methanol was performed the highest value, which is 937.67 mg of butylated hydroxytoluene (BHT). Conclusion: Different active compounds present in the extracts may contribute different cytotoxicity effects of crude extracts. The relationship data of total phenolic, total flavonoid, and cytotoxic potential of C. nutans, indicates that these plants might contain valuable active compounds as a chemotherapeutic agent. Further investigations to elucidate the chemical structures of active compounds are necessary for potential compounds discovery in drugs.